Insularity effects on bird immune parameters: A comparison between island and mainland populations in West Africa. Issue 11 (14th April 2017) - Lobato, Elisa; Doutrelant, Claire; Melo, Martim; Reis, Sandra; Covas, Rita
Abstract: Oceanic islands share several environmental characteristics that have been shown to drive convergent evolutionary changes in island organisms. One change that is often assumed but has seldom been examined is the evolution of weaker immune systems in island species. The reduction in species richness on islands is expected to lead to a reduced parasite pressure and, given that immune function is costly, island animals should show a reduced immune response. However, alternative hypotheses exist; for example, the slower pace of life on islands could favor the reorganization of the immune system components (innate vs. acquired immunity) on islands. Thus far, few island species have been studied and no general patterns have emerged. Here, we compared two immune parameters of birds from São Tomé and Príncipe islands to those of their close relatives at similar latitudes on the mainland (Gabon, West Africa). On islands, the acquired humoral component (total immunoglobulins) was lower for most species, whereas no clear pattern was detected for the innate component (haptoglobin levels). These different responses did not seem to arise from a reorganization of the two immune components, as both total immunoglobulins and haptoglobin levels were positively associated. This work adds to the few empirical studies conducted so far which suggest that changes in immune parameters in response to insularity are not as straightforward as initially thought. Abstract : We report a comparison of two immune parameters of bird species from São Tomé and Príncipe islands to those of close relatives on the mainland (Gabon, West Africa). Overall, our study provides indication of lower antibody levels as an immune phenotype on islands but no overall changes in haptoglobin levels which suggest a more complex response of immunity to insularity than previously thought.